Aplikasi Berbasis Web untuk Penjualan, Pembelian dan Manajemen Persedian Menggunakan Metode FIFO (Studi Kasus: Toko Pompi Songket, Medan) - Nikita Oktavia Yolanda Sihombing; Anak Agung Gde Agung; Eti Suprihatin (Universitas Telkom, 2024)
Pompi Songket Shop is a Micro, Small and Medium Enterprise (MSME) which operates in the field of selling songket, ulosand kebaya woven cloth. Sales are still done manually. This recording can cause errors in the recording system, therebyaffecting the preparation of financial reports. With the development of technology, an application was built that can help thesales process. This application can help owners and employees who work there to create valid data. This application wascreated using the CodeIgniter Framework programming language and MySQL database. F unctionality tested using theBlackbox Testing method